2016
DOI: 10.2334/josnusd.58.59
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MMP2 and MMP9 expression levels between primary and metastatic regions of oral squamous cell carcinoma

Abstract: Matrix metalloproteinases (MMPs)and tumor-associated macrophages (TAMs) play important roles in tumor growth. The present study investigated the expression levels of MMP2 and MMP9 in relation to the distribution of TAMs in the primary and metastatic regions of oral squamous cell carcinoma. Twenty-nine cases of oral squamous cell carcinoma (OSCC) with regional lymph node metastasis were selected from available documents in the archives of the Department of Pathology, Nihon University School of Dentistry. Four-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…and MMP9. Previous studies have shown that inhibition of the production and downregulation of MMP2 and MMP9 in colorectal cancer can play an anti-metastasis role [39]. We revealed that knockdown of KIFC1 resulted in a reduction of MMP2 and MMP9 of PTC cells, which agrees the results of previous studies [40,41].…”
Section: Discussionsupporting
confidence: 92%
“…and MMP9. Previous studies have shown that inhibition of the production and downregulation of MMP2 and MMP9 in colorectal cancer can play an anti-metastasis role [39]. We revealed that knockdown of KIFC1 resulted in a reduction of MMP2 and MMP9 of PTC cells, which agrees the results of previous studies [40,41].…”
Section: Discussionsupporting
confidence: 92%
“…There are accumulating evidences that Bcl2 plays a pivotal role in chemoresistance and metastasis (Kallel‐Bayoudh et al ., ; Bold et al ., ), and also, MMPs are closely involved in metastasis (Deryugina and Quigley, ). Consistent with wound healing assay data, Dehydrocorydaline attenuated mRNA levels of MMP7 (Li et al ., ) and MMP9 (Nishio et al ., ) as metastasis biomarkers in H1299 cells by qRT‐PCR, and also, protein expression of Bcl2 was attenuated in a concentration‐dependent fashion in NSCLCs, implying the crucial roles of MMPs and Bcl‐2 signaling.…”
Section: Discussionmentioning
confidence: 91%
“…An increased MMP1 expression level was detected in patients with OSCC compared with that in healthy controls and was related to metastasis . The expression levels of MMP2 were notably elevated in the metastatic regions of OSCC compared with those in the primary region . The epithelial‐mesenchymal transition related molecules, VIM and CDH1 , were significantly associated with lymph node metastasis and patient survival in OSCC .…”
Section: Discussionmentioning
confidence: 95%